How long do you need to treat bacteremia in a stable patient?. Issue 2 (February 2017) - Curtis, Troy; Devitt, Jessica
Abstract : CASE : A 57‐year‐old man with a history of type 2 diabetes mellitus, hypertension, and chronic lower extremity edema was admitted to the hospital with redness, swelling, and pain around a right lower extremity ulcer. He was initially found to have a fever and tachycardia, which resolved with IV fluids and acetaminophen. Blood cultures revealed Staphylococcus aureus and the patient was started on appropriate antibiotic therapy. How long should antibiotic therapy be administered to this patient?